Dampak Negatif Pemilihan Kepala Daerah Langsung dan Pemilihan Kepala Daerah melalui DPRD serta Pemilihan Kepala Daerah Ideal - Hakim, Setiawandi (Sawala : Jurnal Administrasi Negara, 2018)
The election of the regional head is certainly only one final goal, namely in order to achieve the welfare of the community. It does not produce damage, chaos, corruption and loss of life. So it is necessary to do a review to find the ideal solution for the election of the regional head. Research methods: The study of literature with qualitative descriptive models is used in this paper in outlining the answers to the problems of election / recruitment of regional heads. With the many negative impacts / badness of Direct Election and Regional Head Election through DPRD, the purpose of the State and the objective of the Government to form Local Government is to make the community prosperity difficult to achieve; Both the direct election of regional heads and the election of regional heads by the DPRD have negative impact / badness, such as many cases of riots, causing casualties, high costs so as to burden the APBN / APBD, money politics, horizontal conflicts in the community is very high, many cause problems (corruption case). Lack of selected KDH capability and Abuse of authority by KDH selected from incumbent candidates; The selection (recruitment) of the head of the region through the selection of candidates who are capable and qualified and have good moral and integrity is known and familiar with the community and the region is the ideal pattern of recruitment of the regional head